2023
DOI: 10.1186/s13102-023-00703-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and net meta-analysis of the effects of different warm-up methods on the acute effects of lower limb explosive strength

F. Y. Li,
C. G. Guo,
H. S. Li
et al.

Abstract: Objective To evaluate the effects of different warm-up methods on the acute effect of lower limb explosive strength with the help of a reticulated meta-analysis system and to track the optimal method. Methods R software combined with Stata software, version 13.0, was used to analyse the outcome metrics of the 35 included papers. Mean differences (MD) were pooled using a random effects model. Results 1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Dynamic stretching gives an edge to the dynamic stretching group over the PNF stretching group. This result is backed by the data from numerous studies, which demonstrated an acute increase in power, sprint, or jump performance after dynamic stretches [20,24]. Dynamic stretching includes varieties of movements that are then combined with stretch movement.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Dynamic stretching gives an edge to the dynamic stretching group over the PNF stretching group. This result is backed by the data from numerous studies, which demonstrated an acute increase in power, sprint, or jump performance after dynamic stretches [20,24]. Dynamic stretching includes varieties of movements that are then combined with stretch movement.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that engaging in dynamic stretching exercises can lead to enhancements in physical activity performance, specifically in areas such as vertical jump performance and leg extension power [ 18 , 19 ]. Numerous studies also demonstrated an acute increase in power, sprint, or jump performance after dynamic stretches [ 20 , 21 , 22 , 23 , 24 ]. However, some studies contradict the idea that dynamic stretching is effective for performance development, such as by Nelson et al [ 13 ], who found that dynamic stretching reduces the performance output of knee strength.…”
Section: Introductionmentioning
confidence: 99%